PELESTARIAN BENDA CAGAR BUDAYA DI OBJEK WISATA MUSEUM SANG NILA UTAMA PROVINSI RIAU - Martina Butar-butar; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aims to determine the Preservation of Cultural Heritage Objects Museum Sang Nila Utama Riau Province. By using the theory of culture and tourism minister rules of preservation of cultural heritage objects and sites, using two-way preservation, namely the protection and maintenance.This research’s uses descriptive qualitative methods to analyses the problems that were raised. The sample this research were department heads and staff of the field of conservation and preparation as well as the staff of the head of a collection by using purposive sampling. Data gathering tools used were observation and interviews.Based on the results of research in the Preservation of Cultural Heritage Objects Museum Sang Nila Utama Riau Province. Still very far from a decent museum that is attributable to the presence of flaws in the supporting facilities and personnel competent museum in the record and preserve the cultural heritage objectsKey words: the Preservation of Cultural Heritage Objects, Museum Sang Nila Utama Provinsi Riau.